Analysis the Implementation Digital-Based Nursing Information System with Nurses' Job Satisfaction and Patients' Satisfaction - Nuryati, Nuryati; Santoso, Windu; Ibnu, Faisal; Azizah, Lilik Ma'rifatul; Zamroni, Asroful Hulam (GLOBAL HEALTH SCIENCE GROUP, 2024)
The implementation of digital-based information systems in nursing care documentation has been widely implemented in hospitals. However, nurses are still dissatisfied because they feel burdened by the digital system and this impacts patient satisfaction in receiving nursing care. Therefore, analysis is needed regarding the implementation of a digital-based nursing information system with nurse job satisfaction and patient satisfaction in hospitals. This study used a cross-section comparative design with a sample of 222 nurses and 222 patients. The sample was selected using a simple random sampling technique. Data collection using a questionnaire includes the independent variable in the form of the implementation of a nursing information system and the dependent variable in the form of nurse job satisfaction and patient satisfaction. Data were analyzed using the independent t-test with a p-value ≤ 0.05. Research results from the independent t-test statistical test. The p-value is 0.000 < 0.05, so according to the basis of decision-making in the test it can be concluded that H0 is rejected, which means there is a difference in average between nurse job satisfaction and patient satisfaction in the implementation of a digital-based nursing management information system in nursing services in the Inpatient Room RSUD Dr. Soetomo Surabaya. Implementation of a digital nursing information system provides nurses with effectiveness and efficiency in carrying out their duties. This makes the workload of nurses lighter increases the productivity of the quality of nursing received by patients and has an impact on patient satisfaction. Nursing management is expected to improve the implementation of supervision of nursing care documentation by looking at the completeness and suitability of SOPs in the nursing information system (SIK). In addition, nursing management needs to develop a nursing information system (SIK) model in collaboration with the hospital information technology team so that nurses are effective and efficient in implementing nursing care documentation.